Desenvolvimento de misturas prontas para mingau sem glúten a base de farinhas de babaçu (Attalea speciosa), banana (Musa ssp.) e abóbora (Cucurbita sp.) - SOARES, Milka Vitor (2023)
The gluten-free foods consumption is a global trend, but most of the products currently on the market have characteristics of low technological quality, high sugar and fat content and low amounts of fiber and minerals. Therefore, there is a demand for the development of products with different types of flour to try to achieve the necessary nutritional and technological quality. Thus, the aim of this study was to produce ready-made mixtures for gluten-free porridge based on babassu mesocarp (Attalea speciosa), banana peel (Musa ssp.) and pumpkin seed (Cucurbita sp.) flours and evaluate their quality. nutritional, technological and sensorial. From babassu mesocarp (BMF), banana peel (BPF) and pumpkin seed (PSF) flours, four ready-mix formulations for porridge were produced (F1 – 100% BMF; F2 – 70% BMF + 20 % BPF + 10% PSF; F3 – 70% BMF + 15% BPF + 15% PSF; F4 – 70% BMF + 10% BPF + 20% PSF). The flours and mixtures were subjected to analysis of composition, physical- chemical characteristics, color (L*, a*, b*), technological and functional properties, as well as microbiological evaluation and subsequently sensory analysis of the prepared porridges. The results demonstrated that the moisture content of all flours and mixtures was within the limit established by legislation; all mixtures have a higher content (p<0.05) of lipids, proteins, ash and fiber compared to the control, probably due to the addition of BPF and PSF, which are rich in such constituents. For the phenolic compounds and antioxidant activity, BMF, BPF and PSF had lower results than those reported in the literature, but it was observed that the mixture of flours (F2, F3, F4) increased the content of phenolic compounds, probably due to some synergistic effect between them that caused greater release of these components. BMF, BPF, PSF showed good emulsifying activity and emulsion stability; F2, which had the highest percentage of BPF in its composition, had a greater gel formation capacity, probably due to the amount of fibers. For the porridge sensorial analysis, although F1 was better accepted, all formulations were in the acceptance zone of the hedonic scale. Moreover, the study demonstrated that the use of the mixed flours provided difference in the sweetness of the porridges, because the consumers considered that F2, F3 and F4 were more suboptimal than F1, which contained only BMF. Another important point is that the consistency of F1 was considered just-about-right, while the other formulations were considered suboptimal for this parameter, indicating that perhaps a higher percentage of flour was needed in relation to the amount of milk in F2, F3 and F4. The porridge mixes exhibited good nutritional, technological and sensory characteristics, indicating that they can be promising alternatives for the production of gluten-free foods.